2017
DOI: 10.30699/jidai.29.2.44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remin Pro and Neutral Sodium Fluoride on Enamel Microhardness After Exposure to Acidic Drink

Abstract: Background and Aim: High consumption of carbonated diet soda is the most common etiologic factor for dental erosion. The purpose of this study was to evaluate the microhardness of the enamel surface eroded by cola after treatment with Remin Pro and neutral sodium fluoride. Materials and Methods: This in vitro experimental study was performed on 20 extracted premolars with no corrosion, abrasion, crack or hypocalcification. To properly evaluate the microhardness, the buccal surface of samples was polished with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
3
6
1
Order By: Relevance
“…This was in line with previous reports on this material [5,6]. It should also be noted that, as mentioned earlier, xylitol, hydroxyapatite, and fluoride can be effective in the decrease of surface roughness by inducing supersaturation of calcium and phosphate ions to promote remineralization, filling porous area, forming a protective film on the tooth surface, and inhibiting the adhesion of bacterial plaque [22]. Hydroxyapatite fills superficial enamel lesions and irregularities that arise from surface demineralization.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This was in line with previous reports on this material [5,6]. It should also be noted that, as mentioned earlier, xylitol, hydroxyapatite, and fluoride can be effective in the decrease of surface roughness by inducing supersaturation of calcium and phosphate ions to promote remineralization, filling porous area, forming a protective film on the tooth surface, and inhibiting the adhesion of bacterial plaque [22]. Hydroxyapatite fills superficial enamel lesions and irregularities that arise from surface demineralization.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have shown that Remin Pro can be absorbed by saliva pellicle, creating an enriched reservoir of calcium that is able to increase remineralization. Furthermore, Remin Pro can increase microhardness [5,6,22]. In the current study, surface roughness after exposure to acid was increased in the two groups, but in Remin Pro groups, this enhancement of surface roughness was less than the initial surface roughness.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…A remineralization treatment regimen (Remin Pro and Clinpro) was applied two times a day for three minutes as per the manufacturer's recommendations to make it clinically relevant [19,20]. The efficiency was evaluated at 14 days as it takes a minimum of 14 days for any toothpaste/cream to express its desired therapeutic effect [21].…”
Section: Discussionmentioning
confidence: 99%